EXPLORING MODERN EDUCATIONAL THEORIES: A LITERATURE REVIEW OF STUDENT LEARNING IN THE DIGITAL AGE - Ismail Ismail (Asosiasi Dosen Muda Indonesia, 2024)
This study aims to examine the application of modern educational theories, namely Connectivism, Humanism, Cognitivism, and Constructivism, to the learning process of students in the digital era. Through literature studies, this study traces how these four theories contribute to shaping a more relevant and practical learning approach amid the rapid development of digital technology. The theory of Connectivism emphasizes the importance of digital networks and global access to information, allowing students to learn through social and digital connections. Humanism focuses on developing individual potential, emotional well-being, and personalized learning. Cognitivism highlights mental processes in information processing, reinforced with technology that helps students manage and store information effectively. Meanwhile, Constructivism emphasizes experiential learning and social interaction, which is realized through collaborative tools and virtual simulations in the digital era. This study integrates findings from the relevant literature to provide a comprehensive perspective on how these theories complement each other and can be optimized in a digital-based education system. The conclusion of this study underscores the importance of combining the best aspects of each theory to create an adaptive, flexible, and student-centered learning approach to face the challenges of education in the digital age.